Floristic and conservation studies of pteridophytes of Maidan Region, Tirah, Khyber Agency, Pakistan - Aziz, Tariq; Gull, Alia; Alam, Jan; Qaiser, Muhammad (International Journal of Applied and Experimental Biology, 2024)
This study was designed to investigate the floristic diversity of the pteridophytes of Maidan Region, Tirah, Khyber Agency, Pakistan. The research activities were carried out in various phases. Before starting the field-related research activities, a detailed field program was designed. Information regarding the respective taxa was obtained through several field surveys. During field surveys, about 200 specimens were collected with proper information. The collected plant specimens were then authentically identified with internationally well recognized floras. Twenty-nine (29) species were identified under 7 genera and 6 families. Of these, one species, i.e., Asplenium hainanense was new to Pakistan. For families, Aspleniaceae was the dominant family with 17 species (58.62%). For the remaining families, less than 6 species were recorded for each. Asplenium was the largest genus with 17 species (58.62%). Altitude-wise, 7 species (24.13%) were recorded between 600-1500 m and minimum number of species were seen in the range between 4000-4500 m. Some promising threats, i.e., land modification for agricultural purposes, stone excavation, fire in the forest land, overgrazing, and deforestation were identified as causing adverse effects on the species explored. These factors should be reduced in order to protect the taxa from local extinction. Serious conservation measures are necessary to avoid eradication of the species from the study area.